2008
DOI: 10.5194/acp-8-7255-2008
|View full text |Cite
|
Sign up to set email alerts
|

SO<sub>2</sub> oxidation products other than H<sub>2</sub>SO<sub>4</sub> as a trigger of new particle formation. Part 2: Comparison of ambient and laboratory measurements, and atmospheric implications

Abstract: Abstract. Atmospheric new particle formation is generally thought to occur due to homogeneous or ion-induced nucleation of sulphuric acid. We compare ambient nucleation rates with laboratory data from nucleation experiments involving either sulphuric acid or oxidized SO 2 . Atmospheric nucleation occurs at H 2 SO 4 concentrations 2-4 orders of magnitude lower than binary or ternary nucleation rates of H 2 SO 4 produced from a liquid reservoir, and atmospheric H 2 SO 4 concentrations are very well replicated in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 35 publications
3
29
0
Order By: Relevance
“…S8) from the gaseous H 2 SO 4 concentration and compares this with ambient observations from the boreal forest in Hyytiälä, Finland (7). The scatter of the atmospheric nucleation rates is attributed to varying temperature, humidity, or varying contributions of unknown species in the nucleation process (29). Our laboratory data agree surprisingly well with nucleation rates observed in the atmosphere.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…S8) from the gaseous H 2 SO 4 concentration and compares this with ambient observations from the boreal forest in Hyytiälä, Finland (7). The scatter of the atmospheric nucleation rates is attributed to varying temperature, humidity, or varying contributions of unknown species in the nucleation process (29). Our laboratory data agree surprisingly well with nucleation rates observed in the atmosphere.…”
Section: Resultssupporting
confidence: 69%
“…First, a nonlinear regression analysis was applied to our data as suggested by ref. 29. As the nucleation rate may depend on both H 2 SO 4 and NucOrg, Eq.…”
Section: Disentangling the Roles Of Sulfuric Acid And Organic Compounmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental finding that high NO concentrations can suppress nucleation was taken as an argument supporting the potential role of HSO 5 (Friend et al, 1980;Berndt et al, 2008;Laaksonen et al, 2008). Very recently, Sipilä et al (2010) showed experimentally that with the help of high efficiency particle counters (Sipilä et al, 2009;Vanhanen, 2009) new particle formation can be observed in the laboratory for H 2 SO 4 concentrations down to ∼10 6 molecule cm −3 .…”
Section: Introductionmentioning
confidence: 92%
“…1106 F. Khosrawi et al: Particle nucleation in the Arctic free troposphere ion-mediated or ion-induced nucleation (e.g., Yu and Turco, 2000;Lee et al, 2003;Lovejoy et al, 2004;Curtius et. al., 2006;Laaksonen et al, 2008). Laboratory experiments have suggested that in polluted areas nucleation of new particles may even take place inside clouds through condensation of organic vapors .…”
Section: And Thementioning
confidence: 99%